INDIGENOUS LEGACY LEGAL PHENOMENONS IN INDONESIA BETWEEN LEGAL JUSTICE AND SOCIAL JUSTICE - Ubaidillah, M. Burhanuddin (Prodi Ahwal al-Syakhsiyah STAI Darussalam Nganjuk, 2020)
Legal justice and social justice as two different concepts form the basis of the development of theoretical law and practical law. The pluralistic fact of customary inheritance law that is not single in Indonesia and is subject to genealogical and territorial alliance, is not written in legislative regulations (unstatutery law), and has been generally believed (taken for granted) in reality is very difficult to integrate. Even now customary law cannot be realized in legal unification and there is still no uniform national regulation in Indonesia due to the clash of cultural, religious and sociological complications. This is where the urgency of the concept of legal justice and social justice develops his theory in improving the law so that the phenomenon of customary inheritance law gets an alternative solution based on the social structure of a pluralistic Indonesian society.